Accuracy of repeated measurements of late‐night salivary cortisol to screen for early‐stage recurrence of Cushing's disease following pituitary surgery. (25th July 2014) - Danet‐Lamasou, Marie; Asselineau, Julien; Perez, Paul; Vivot, Alexandre; Nunes, Marie‐Laure; Loiseau, Hugues; San‐Galli, François; Cherifi‐Gatta, Blandine; Corcuff, Jean‐Benoît; Tabarin, Antoine
Summary Objective The performance of late‐night salivary cortisol (LNSC) to accurately screen for postoperative recurrence of Cushing's disease (CD) at an early stage is unknown. The aim of this study was to compare the accuracy of multiple sampling strategies to suggest the optimal number of LNSC samples needed for diagnosing post‐surgical recurrences of CD at an early stage. Design Retrospective analysis in a single centre. Patients and measurements Thirty‐six patients in surgical remission of CD had successive measurements of LNSC, defined as 'sequences', using a locally modified RIA assay as part of long‐term follow‐up (69·2 ± 10·6 months). Patients underwent an extensive biochemical evaluation within 3 months before or after a sequence of saliva sampling and were classified as being in remission or in early‐stage recurrence. The accuracy of three diagnostic strategies combining two, three or four LNSC results from a sequence was estimated using areas under the ROC curves (AUC), sensitivity, specificity and predictive values. Results Forty‐four sequences of LNSC measurements were available. Fifty‐two percent of sequences were performed during early‐stage recurrence. The intrasequence variability of LNSC was higher during recurrence than during remission (medians of SDs: 2·1 vs 0·5 nm; P < 0·0001). AUCs from ROC curves ranged from 0·93 to 0·96 depending on the strategy. For 90% sensitivities, the best specificities (92·9% and 90·9%) were achieved by strategies taking into account three or four measurements summarized either by their mean or their maximum value. Conclusions Increase in LNSC concentration is an early abnormality during post‐surgical recurrence of CD. However, due to a major within‐patient variability of LNSC from 1 day to another, a screening strategy using three or four samples collected on successive days may be recommended to detect early‐stage recurrence of CD with a high accuracy.